Clinical features and outcome of acquired haemophilia A - Gheisari, R.; Bomke, B.; Hoffmann, T.; Scharf, R. E. (Hämostaseologie, 2010)
We have performed a monocenter study on 29 consecutive patients with acquired haemophilia A who were referred for diagnosis and treatment to the Düsseldorf Haemophilia Comprehensive Care Center between March 2001 and February 2010. Patients, methods: 18 men (age: 44–86 years) and 11 women (age: 20–83 years). For laboratory evaluation, a standardized staged protocol of aPTT, FVIII : C activity and concentration, mixing studies with patient and normal plasma, and quantification of inhibitor titers (Bethesda assay) was used. Diagnostic work-up included elaborate examinations for any underlying disease. Results: In 18 (62%) of the 29 patients with acquired haemophilia A, an underlying disorder was identified, including 9 patients with respiratory diseases (31%), 7 patients with autoimmune disorders (24%), one with malignancy, and one with postpartum state, while in 11 patients (38%) acquired haemophilia A remained idiopathic. Haemotherapy of bleeding, suppression or elimination of the inhibitor, and induction of immunotolerance to endogenous FVIII:C were performed according to a treatment algorithm. Predefined clinical endpoints were control of bleeding, eradication of the inhibitor, complete or partial remission (CR, PR), relapse, or early death (≤30 days). Of the 29 patients in total, 22 individuals achieved CR (76%), three had PR, one relapsed, and three died within 30 days (one of acute myocardial infarction while on anti-haemorrhagic treatment, one of sepsis while on immunosuppression due to active acquired haemophilia A, one of lung bleeding in association with pre-existing pulmonary sarcoidosis). Conclusion: This monocenter study demonstrates that control of life-threatening bleeding, eradication of the inhibitor, and induction of tolerance to endogenous FVIII have significantly improved the clinical outcome of acquired haemophilia A. Our data also suggest a shift in underlying disorders associated with acquired haemophilia A, whereby, in comparison to published studies, a relative increase in the proportion of patients with respiratory diseases is present.
Keywords: Acquired haemophilia A; autoantibodies; morbidity; mortality; underlying disorder